DINAMIKA IMPLEMENTASI PROSEDUR KEAMANAN PENERBANGAN: STUDI MULTI-PERSPEKTIF DI BANDARA INTERNASIONAL SAM RATULANGI MANADO - Sazli Nur Chalis Djafar; Ogi, Imelda W. J.; Palandeng, Indrie Debbie (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to analyze the gap between international and national aviation security regulations and field-level operational practices through a multi-perspective study. Adopting a qualitative approach with a phenomenological design, data were collected through in-depth interviews, participant observation, and document analysis at Sam Ratulangi International Airport, Manado. The findings reveal the existence of